Correction: Mitochondrial Uptake of Thiamin Pyrophosphate: Physiological and Cell Biological Aspects - Subramanian, Veedamali S.; Nabokina, Svetlana M.; Lin-Moshier, Yaping; Marchant, Jonathan S.; Said, Hamid M. (PLOS ONE, 2017)
null